PLASTIC / NYLON WASTE POLLUTION AND DISPOSAL IN OYO STATE, NIGERIA - Bolaji K.A.; Kabir G.B.; Adebayo D.O.; Oguntoye T.O. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
This study examined the effect of plastic/nylon pollution, the disposal method and the factors influencing the methods of disposal in Oyo state. This study was conducted in eleven local government areas (LGA) of Oyo states using structured questionnaire with five hundred respondents purposively selected but 454 questionnaires were valid for the research analysis. The analytical tools used were descriptive statistics (such as percentage and frequency) and multinomial regression model. Majority (81%) of the respondents were married, about 88.6% of the respondents were educated. Most (84%) of the sampled households had a family size of between 1 and 5 with almost 60% of the respondents earning between ₦10,000-₦50,000. The study observed that 54% of the respondents’ choice of plastic and nylon disposal methods was time savings, about 86% had no difficult in disposing their waste, 29.5% of the respondents stated that plastic and nylon waste disposal block water ways. The factors influencing plastic/nylon disposal were waste collectors (p<0.01), House ownership (p<0.05) and educational status (p<0.05). The Negelkerke R2 indicates that 49% of the variation in the factors influencing plastic/nylon disposal is explained by the model. It is therefore recommended that more awareness should be made about plastic/nylon pollution and proper disposal. Then alternative packaging materials and reuse of plastic/nylon should be encouraged due to the difficulty in disposal.